OBEDIENCE TO LAW AND STATE LEGITIMACY: AN ANALISIS OF THE THEORY OF NATUAL DUTY OF OBEYING JUST INSTITUTIONS ACCORDING TO JEREMY WALDRON - Cesar Baena (Revista Eletrônica do Curso de Direito da UFSM, 2017)
This paper analyzes the plausibility of the theory of the natural duty of obeying just institutions, as a justification of the obligation to obey the law, according to Jeremy Waldron. So, the work points that this theory is based on an approach of procedural legitimacy, i.e. one according to which the democratic procedure has an intrinsic value derived from respect for political equality and the equal right to participation. Based on the arguments that are aimed at demonstrating the natural duty to obey the institutions that resolve our conflicts, within the framework of what Waldron calls the "circumstances of politics", it can be shown that it is possible to justify not only the legitimacy of the decisions of a democratic state, but also political obedience to the law.